PROSES MEDIASI KE MOMEN MORAL Dalam “Pemahaman Diri” Ricoeur dan “Penampakan Wajah” Levinas - Haryatmoko . (Studia Philosophica et Theologica, 2009)
The focus of this paper is the convergence of Paul Ricouer’s and Emmanuel Levinas’ thoughts concerning the moral responsibility. The role of the mediation between subject and self-understanding would be an appropriate starting point to elaborate such an inquiry. The self-understanding which is one of the hermeneutical categories, according to Ricoeur, represents a decisive moment of the moral awareness. While in the Levinas’ perspective, the appearance of the face constitutes the birth of the moral awareness. Despite this convergence, there is a different approach between both philosophers. Ricoeur’s starting point is text and ego, while Levinas’ thought is based on the ‘other’. So there is a radical difference in the status of alterity which has an implication in the cognition and activity. Levinas refutes the ontology and emphasizes on ethics as experience. While Ricoeur aims at the conditions of possibility of an adequate interpretation which enables to better understand himself/ herself. The concept ‘better self-understanding’ integrates the epistemological and ontological dimensions.